The graphene oxide species induce a different biological response in SN4741 Parkinson cell line - Rodríguez-Losada, Noela; Wendelbo, Rune; Aguirre-Gómez, José Ángel; Ocaña Farfán, María del Carmen; Arráez-Sánchez, Miguel Ángel; Díaz-Casares, Amelia; Medina-Torres, Miguel Ángel; Martínez-Moreno, José Manuel; Arenas, Ernest; Narváez-Bueno, José Ángel (My University, 2019)
Introduction: Graphene Oxide (GO)has recently emerged as a reliable material to create scaffolds for the neural tissue because of its biocompatibility, electroconductive and physicochemical properties. Graphene is a 2-dimensional material consisting of rings of carbon atoms with an excellent electrical conductivity originating in the sp2 hybridized carbons network. Nevertheless, there is not a consensus which kind of graphene oxide is most useful of benefit.
Keywords: Parkinson, Enfermedad de - Tratamiento; Óxido de grafeno - Aplicaciones; Óxido de grafeno - Propiedades; Graphene; Parkinson